Flow design for migrating fish - Lindmark, Elianne (Luleå tekniska universitet, Strömningslära och experimentell mekanik, 2008)
The utilization of rivers for hydropower production leads to problems for migrating fish, such as Atlantic salmon (Salmo salar) and sea trout (Salmo trutta). Both salmon and trout reproduce in fresh water, but spend their adult years at sea. To overcome man-made obstructions to and from the spawning grounds the fish needs help. Fishways for upstream migrating fish is an old technique; however the efficiency is often low due to inefficient attraction water. The upstream migrating fish are attracted to high water velocities and often approach the dominating flow from the turbine outlet instead of entering the fishway. For the downstream migrating smolt (young fish) the only way to pass a power plant is often via the turbines, with a high mortality as a result. The smolt follow the main flow in the river on the way downstream avoiding high accelerations or retardations. This thesis covers investigations on both an attraction channel to increase the water velocity at the inlet of a fishway for upstream migraters and a smolt guidance device to guide the smolt away from the turbine inlet to a safer passage route. To investigate the properties of the attraction channel both model and field experiments have been carried out, as well as numerical studies. The velocity in the channel has been examined with Laser-Doppler-Velocimetry and the flow field in the channel was studied using Particle-Imaging- Velovimetry. The results show that the water can be accelerated 38 % compared with the surrounding velocity. How far the increase in velocity is present depends on the depth of the attraction channel. The field tests carried out at Sikfors hydropower plant in Piteå River (Sweden) show that the fish do swim through the channel, providing that the channel is black. The flow around a smolt guidance device has been studied using numerical simulations. The aim of the device is to redirect the surface flow from the turbines to the spillway. By doing this, the shallow swimming smolt will also be guided towards the spillway and a ...